Connecting offshore wind farms to the electric power system: A brief overview - Carvalho, Paulo Fernando Santos Dias de; Schiochet, André Fernando; Rocha, Leonardo de Carvalho; Borges, Thiago Trezza; Monteiro, Paulo Roberto Duailibe (Seven Editora, 2023)
This paper presents an overview of the implementation of the main wind farms Offshore carried out so far, most of which is in Europe. A summary of the solutions applied and consolidated in the industry, related to the transmission technologies used in the connection of wind farms Offshore to existing power grids is shown. Some of the topics covered are: the type of transmission used (direct or alternating current), the technology adopted in the converter bridges in the enterprises that chose to use direct current transmission (VSC) and its advantages, the magnitude of the distances and transmission capacities achieved and the technologies for compensation of reactives. In addition, regulatory and economic aspects related to the connection of these wind farms to the transmission grid are also addressed. Finally, a case study is presented in which several alternatives for the connection of two parks are compared Offshore to the transmission system from an economic point of view. DOI:https://doi.org/10.56238/uniknowindevolp-111